La edad mayor de 40 años, el género femenino, el nivel educacional y socio económico bajo, el tratamiento anti tuberculoso previo, diabetes mellitus, contacto MDR y VIH como factores de riesgo asociados a la incidencia de tuberculosis drogo-resistente en adultos hospital I Santa Isabel de el porvenir-MINSA años 2002-2014 - Alvarez Riega, Julio César (2014)
To determine the incidence and risk factors of tuberculosis drug-resiatance in adults. Design: Observational analytical case-control in a cohort Setting: St Elizabeth Hospital of El Porvenir-Trujillo. Subjects: Treated 66 cases of TBDR and 66 controls TB no DR. Results: The incidence of TB-DR during the period was 18.78%. The function of the incidence trend is + 1.343% per year. Female gender was not associated with incidence of TB-DR factor (p = 0.079)...Over 40 years of age was not associated with risk factor for TBD R p = 0.428. The level is and the low level of education were not factors associated with incidence of TBDR. Pretreatment., and. irregular treatment were risk factor for TBMDR the abandonment of treatment ,contact with patient MDR was TBDR risk factor p = 0.000.Diabetes mellitus was TBDR risk factor p = 0.013... Conclusions: Diabetes mellitus, previous treatment, irregular treatment, the abandonment of the treatment and contact with patient MDR were TBDR risk factors